Existence and uniqueness results for compressible Reynolds equation with slip boundary conditions. Issue 2 (25th January 2021) - Bayada, G.; El Alaoui Talibi, M.; Hilal, M.
ABSTRACT: In this paper a one dimensional system describing the behaviour of a thin film flow (lubrication assumption) is analysed for various non linear slip conditions on the solid surface including Tresca shear limited models. So far, existence results for such problems require an incompressibility assumption. In the present work, this assumption is removed, allowing cavitation to be taken into account. The possibility of considering such models including simultaneously cavitation and slip/no-slip conditions is of practical importance as this corresponds to the actual trend in lubrication engineering.